Criteria for Pediatric Sepsis—A Systematic Review and Meta-Analysis by the Pediatric Sepsis Definition Taskforce*. Issue 1 (6th October 2021) - Menon, Kusum; Schlapbach, Luregn J.; Akech, Samuel; Argent, Andrew; Biban, Paolo; Carrol, Enitan D.; Chiotos, Kathleen; Jobayer Chisti, Mohammod; Evans, Idris V. R.; Inwald, David P.; Ishimine, Paul; Kissoon, Niranjan; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: To determine the associations of demographic, clinical, laboratory, organ dysfunction, and illness severity variable values with: 1) sepsis, severe sepsis, or septic shock in children with infection and 2) multiple organ dysfunction or death in children with sepsis, severe sepsis, or septic shock. Data Sources: MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials were searched from January 1, 2004, and November 16, 2020. Study Selection: Case-control studies, cohort studies, and randomized controlled trials in children greater than or equal to 37-week-old postconception to 18 years with suspected or confirmed infection, which included the terms "sepsis, " "septicemia, " or "septic shock" in the title or abstract. Data Extraction: Study characteristics, patient demographics, clinical signs or interventions, laboratory values, organ dysfunction measures, and illness severity scores were extracted from eligible articles. Random-effects meta-analysis was performed. Data Synthesis: One hundred and six studies met eligibility criteria of which 81 were included in the meta-analysis. Sixteen studies (9, 629 patients) provided data for the sepsis, severe sepsis, or septic shock outcome and 71 studies (154, 674 patients) for the mortality outcome. In children with infection, decreased level of consciousness and higher Pediatric Risk of Mortality scores were associated with sepsis/severe sepsis. In children with sepsis/severe sepsis/septic shock, chronic conditions, oncologic diagnosis, use of vasoactive/inotropic agents, mechanical ventilation, serum lactate, platelet count, fibrinogen, procalcitonin, multi-organ dysfunction syndrome, Pediatric Logistic Organ Dysfunction score, Pediatric Index of Mortality-3, and Pediatric Risk of Mortality score each demonstrated significant and consistent associations with mortality. Pooled mortality rates varied among high-, upper middle-, and lower middle-income countries for patients with sepsis, severe sepsis, and septic shock ( p < 0.0001). Conclusions: Strong associations of several markers of organ dysfunction with the outcomes of interest among infected and septic children support their inclusion in the data validation phase of the Pediatric Sepsis Definition Taskforce.